Comparison of knowledge, attitude and practice on haze among first and final year medical students in Universiti Putra Malaysia - Mohd Nasir, Nor Hazwani; Abdul Rahman, Haliza (Life Sciences Society of Pakistan, 2018)
Haze is one of atmospheric pollution that has occurred in Malaysia. Most of the haze episodes occurred in conjunction with period of prolonged drought associated with El Nino phenomenon. Haze gives great negative impacts in terms of health, social and economy. The study aims to know the knowledge, attitude and practice on haze among first and final year of medical students in Universiti Putra Malaysia (UPM). In this cross-sectional study, a total of 244 students were involved as respondents. Questionnaires were administered to determine socio-demographic, information knowledge, altitude and practice on haze among them by using ‘Statistical Package for Social Sciences (SPSS) Version 22.0. Result showed that the level of knowledge for first and final year of medical students was moderate which was 40(41.9%) and 59(39.1%) respectively. The level of attitude for both groups were also moderate, which was 54(57%) and 97(64.2%) respectively. For the practice level, both group showed bad practice during haze, which was 64(68.8%) and 107(70.9%). The findings also indicated that there were no significant difference of mean knowledge, attitude and practice on haze between these two groups (Z=0.555, p>0.05; t= -1.573. p>0.05; Z= -0.720, p>0.05). Malay and Chinese students were associated with knowledge level with odd ratio (OR) 5.22 and 2.98 respectively. In addition, there was an association between knowledge and practice (p=0.003, p<0.005). The attitude level was associated with practice level in which moderate attitude tend to have poor practice on haze (p=0.024, p<0.05). As overall, the medical students perceived moderate knowledge and attitude, but low in practice.